Retinol dehydrogenase 13 deficiency diminishes carbon tetrachloride-induced liver fibrosis in mice. (4th January 2017) - Cui, Xiaofang; Dang, Suying; Wang, Yan; Chen, Yan; Zhou, Jia; Shen, Chunling; Kuang, Ying; Fei, Jian; Lu, Lungen; Wang, Zhugang
Highlights: Rdh13 deficiency reduces liver injury and fibrosis by attenuating hepatic stellate cell activation. Rdh13 deficiency reduces collagen I(II) and TIMP-1 expression during liver fibrosis. Rdh13 deficiency reduces TGF-β1 expression during liver fibrosis. Abstract: Retinol dehydrogenase 13 (RDH13) is a mitochondrion-localized member of the short-chain dehydrogenases/reductases (SDRs) superfamily that participates in metabolism of some compounds. Rdh13 mRNA is most highly expressed in mouse liver. Rdh13 deficiency reduces the extent of liver injury and fibrosis, reduces hepatic stellate cell (HSC) activation, attenuates collagen I (II), tissue inhibitor of metalloproteinase 1 (TIMP-1) and transforming growth factor beta 1 (Tgf-β1) expression. The results indicate an important role of Rdh13 and suggest RDH13 as a possible new therapeutic target for CCl4 -induced fibrosis.